EficientE :um método de dimensionamento econômico para redes de distribuição de água - Carvalho, Paulo Sergio Oliveira de (2007)
It was aimed in the present study to carry out a method of economical measurement of water supply system, composed by pipes network, including its propulsion system. This method is denominated here as EficientE , which was carried out on search of a minimal cost solution for threshed networks, with branches intended to amplify the existing networks. In order to develop the optimization methodology, techniques of dynamic programming were used here, in association with basic economical concepts. This technique-concept association enabled the development of a mathematical algorithm iteration of convergence, aiming to obtain a minimum cost solution. For estimating the variables of state of the system, it was performed for each iteration a special program associated to software of hydraulic simulation of continuous water flow in threshed networks of water supply. The method proposed here was tested in five situations of water networks with distinct features concerning their design, size, and contour conditions. This method showed to be effective in all situations, resulting in excellent performance, which means that it can be applied to networks of water distribution of any proportion, since no restrictions were detected when simulating its application.